2020
DOI: 10.3390/pharmaceutics12121235
|View full text |Cite
|
Sign up to set email alerts
|

The Phospholipid Research Center: Current Research in Phospholipids and Their Use in Drug Delivery

Abstract: This review summarizes the research on phospholipids and their use for drug delivery related to the Phospholipid Research Center Heidelberg (PRC). The focus is on projects that have been approved by the PRC since 2017 and are currently still ongoing or have recently been completed. The different projects cover all facets of phospholipid research, from basic to applied research, including the use of phospholipids in different administration forms such as liposomes, mixed micelles, emulsions, and extrudates, up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 192 publications
0
38
0
1
Order By: Relevance
“…These phospholipids possess the same hydrophobic tail, but are different in hydrophilic heads, which may provide different microenvironments around CsPbBr 3 NCs (Figure 2a). [19,20] Thus, a series of PM-CsPbBr 3 NCs can be obtained by combining different lipid compositions (Figure 2b). In this study, DOPC was chosen as the main component, considering it has been demonstrated to be an excellent stabilizer for a variety of hydrophobic nanomaterials.…”
Section: Effect Of Membrane Compositions On Pm-cspbbr 3 Nanocrystalsmentioning
confidence: 99%
“…These phospholipids possess the same hydrophobic tail, but are different in hydrophilic heads, which may provide different microenvironments around CsPbBr 3 NCs (Figure 2a). [19,20] Thus, a series of PM-CsPbBr 3 NCs can be obtained by combining different lipid compositions (Figure 2b). In this study, DOPC was chosen as the main component, considering it has been demonstrated to be an excellent stabilizer for a variety of hydrophobic nanomaterials.…”
Section: Effect Of Membrane Compositions On Pm-cspbbr 3 Nanocrystalsmentioning
confidence: 99%
“…[49][50][51] Natural biomaterials are desirable in medicinal applications due to their inherent biocompatibility, biodegradability, nontoxicity, nonantigenicity, and bioadhesiveness. [52] The main biomaterials used in transdermal DDS are lipids, [53][54][55][56] hyaluronic acid, [57] and chitosan. [58] Chitosan was employed as NPs, [59,60] microneedles (MN), [61] CPEs, [62] nanofibers, [63] dermal patches and films, [64] and nanogels.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…In particular, DPPC molecules are among PC species comprising hydrophilic head groups (PC) and hydrophobic tails (palmitic acid, Fig. 2) are responsible for reducing surface tension thereby prevents alveoli collapse during the breath process [31]. Other surfactant phospholipids that exist in portions (8-15% total mass) are phosphatidylglycerol (PG) and phosphatidylinositol (PI).…”
Section: Pulmonary Surfactant Compositionmentioning
confidence: 99%